Impacts of ownership changes on emissions and industrial production: evidence from Europe - Chlond, Bettina; Germeshausen, Robert (Discussion paper, 2023)
Firm ownership is a major determinant for the economic performance of firms, and emissions of pollutants are often by-products of industrial production. We investigate the impact of ownership on pollutant emissions of firms and their in- dustrial facilities in Europe jointly with their output, productivity, and other key economic outcomes. To disentangle the influence of ownership from other firm characteristics, we analyse the effects of ownership changes in an event-study approach. We find that industrial facilities and firms decrease their emissions and industrial output after a change in ownership. Emissions intensity and productivity do not change suggesting that reductions in emissions follow proportional reductions in output rather than reflecting changes in pollution abatement technology. We find some evidence for positive spillover effects on productivity and profits of other facilities and firms owned by the acquiring parent company after a change in ownership.
Keywords: Graue Literatur